EVALUASI PRAKTIK KERJA INDUSTRI SEKOLAH MENENGAH KEJURUAN - Malik, Muh. Nasir; Hasanah, Hasanah (Indonesian Journal of Educational Studies, 2015)
The research objective was to evaluate the readiness of the management of the implementation of vocational practice in the industry, The process of implementation, and factors constraints. Evaluative descriptive method CIPP models. The research sample are 12 public and private vocational taken proportionate stratified random sampling. The results showed: (1) evaluation of context is high, namely: (a) the quality of student competence, (b) the suitability of the implementation of the program with school policy, and (c) management readiness is high; (2) evaluation of input is very high, namely: (a) the readiness of student competence, (b) the readiness of the management of the school program, and (c) the readiness of teacher competence; (3) evaluation of the process, namely: (a) the process of implementation of the program running on schedule, but less relevant to the competencies required of students, (b) factors inhibiting factor, the lack of cooperation with the industry; and (4) evaluation of products is quite high, namely: (a) creating a link and match learning in schools, (b) increase student competence